KEPENTINGAN ELIT DALAM PT RIAU AIRLINES TAHUN 2002-2013 - Shariyani "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The interests of elite on PT Riau Airlines Year 2002-2013. PT Riau Airlines (PT RAL) is one of the loss-making enterprises Riau province reached 99%. This number is the highest number compared to 6 other enterprises in the province of Riau. The failed of PT RAL, because there is any the bankruptcy proceeding by one of the vendors. The lawsuit is done because of the amount of debt piling up and is due payment. The influence of the power elite in the form of interests has a very big influence on this situation. This paper aims to describe the forms of these interests. These interests include, rational elite interests and subjective elite interests. The method used is the qualitative method. The results showed that of the overall shape of the interest on the formation and development of PT RAL, there are 10 elite interests subjective and 5 rational elite interests. The dominance of elite interests since the beginning of the establishment of the basis of losses to the failed of PT RAL.Keywords: Interest, rational, subjective